ANALYSIS OF LANGUAGE ATTITUDES TOWARDS INDONESIAN LANGUAGE IN GRADE VIII STUDENTS OF SMP NEGERI 3 SUNGGUMINASA - Sudirman; Andi Sukri Syamsuri; Abdil Munir (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study aims to analyze the language attitudes of grade VIII students of SMP Negeri 3 Sungguminasa and its influence on the use of Indonesian language in learning, especially listening and reading skills. This study uses a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation. Data was obtained from Indonesian teachers, homeroom teachers, and students as the main informants. The results of the study show that students' language attitudes vary, ranging from very positive to less appreciative of the use of Indonesian. Students with a positive attitude are more active in using Indonesian in learning and have better listening and reading skills. On the other hand, students with negative attitudes tend to be passive, less confident, and more dominant in using regional languages in daily communication. Environmental factors, material relevance, teaching methods, and learning experiences greatly influence the formation of students' language attitudes. This study confirms that language attitudes are an important factor in the success of Indonesian language learning. These findings are expected to be the basis for teachers and schools to design learning strategies that are more communicative, contextual, and able to foster students' positive attitudes towards the Indonesian language